A comparison of the effect of 3M Fresnel prisms and Trusetal prism foils on visual function - Stephanie H. Cotton (British and Irish Orthoptic Journal, 2010)
Aim:  To determine any differences in visual acuity (VA) and contrast sensitivity (CS) between 3M Fresnel prisms and Trusetal prisms foils. Methods:  Sixteen participants (mean age 20 years) with normal VA and CS participated. The effect of 5 Δ, 10 Δ, 20 Δ and 30 Δ prism strengths on monocular VA and CS was assessed using a Bailey-Lovie logMAR chart and Pelli-Robson chart, respectively. Measurements were carried out for both 3M Fresnel prisms and Trusetal prism foils. A comparison of the physical properties of the two prism types was made.  Deterioration in VA and CS was evident with increasing prism strength with both prism types. VA was more significantly reduced with 3M Fresnel prisms than with Trusetal prism foils [F1,15 = 19.63, p < 0.001]. There was significant interaction between prism types and prism strength [F3,45 = 10.36, p < 0.0001], due to 30Δ 3M Fresnel prisms reducing VA by 0.13 logMAR more than the Trusetal prism foils. There was no statistically significant difference between the prism types for CS [F1,15 = 2.21, p = 0.1582]. 3M Fresnel prisms were thinner than the Trusetal prism foils. The thicker Trusetal prism foils consist of fewer bases per centimetre but were more difficult to fit to spectacle lenses. Conclusions:  There is no difference in VA or CS regardless of whether a 3M Fresnel prism or Trusetal prism foil is used until 30Δ, when Trusetal prism foils give better VA. For large deviations it may therefore be more beneficial for the patient to use a Trusetal prism as part of their treatment plan.